Impaired regulation of portal venous flow in response to a meal challenge as quantified by 4D flow MRI. Issue 4 (October 2015) - Roldán‐Alzate, Alejandro; Frydrychowicz, Alex; Said, Adnan; Johnson, Kevin M.; Francois, Christopher J.; Wieben, Oliver; Reeder, Scott B.
<x xml:space="preserve">Abstract</x> Purpose Portal and mesenteric hemodynamics is greatly altered in portal hypertension patients. This study utilizes 4D flow magnetic resonance imaging (MRI) to visualize and quantify changes in abdominal hemodynamics in patients with portal hypertension undergoing meal challenge. Materials and Methods Twelve portal hypertension patients and six healthy subjects participated in the study. Baseline MRI was acquired after 5 hours of fasting. Postmeal MRI was obtained 20 minutes after subjects ingested EnSure Plus (574 mL). Imaging was performed at 3T using 4D flow MRI with an undersampled radial acquisition. Flow measurements were performed blinded to subject status (fasting/meal). Flow values for each vessel were compared before and after the meal challenge using paired Student's t‐tests (P < 0.05). Results After meal challenge, significant increases in blood flow were observed in supraceliac aorta, portal vein, superior mesenteric vein, and artery in both groups (P < 0.05). In patients, hepatic artery (P = 0.001) and splenic vein (P = 0.045) flow decreased while azygos vein flow (P = 0.002) increased. Conclusion Portal venous flow regulation to adjust the increasing mesenteric venous flow after a meal challenge may be impaired in patients with cirrhosis. The ability to comprehensively quantify the hemodynamic response of the abdominal vasculature to a meal challenge using 4D flow MRI reveals the potential of this technique to noninvasively characterize portal hypertension hemodynamics. J. Magn. Reson. Imaging 2015;42:1009–1017.